Clinically useful flow cytometry approach to identify immunophenotype in acute leukemia. Issue 4 (April 2019) - Ouyang, Guifang; Xu, Zhijuan; Jiang, Danjie; Zhu, Huiling; Wang, Yi; Wu, Wenmiao; Sun, Yongcheng; Sheng, Lixia; Xu, Kaihong; Lou, Yanru; Mu, Qitian; Zhang, Yi; et al.
Objectives: Acute leukemia (AL) is a highly heterogeneous malignant disease caused by hematopoietic cell abnormalities. Our study investigated the potential for immunophenotyping of leukemic cells via flow cytometry and the clinical usefulness of this approach in treatment of AL. Methods: Bone marrow (BM) specimens were collected to detect antigen expression on hematopoietic cells in pre-treatment samples from patients with AL. In addition, fraction survival curves were calculated using the Kaplan-Meier method to explore the effect of markers on prognosis in AL. Results: Expression levels of immunophenotypic markers in patients with acute lymphoblastic leukemia (ALL) were significantly different from those in patients with acute myeloid leukemia (AML). In addition, there was a potential association between the surface marker, cluster of differentiation 2 (CD2), and fraction survival in AML. However, no similar result was found in ALL. Moreover, genetic tests showed greater positive variation of the break point cluster-Abelson tyrosine kinase ( BCR-ABL ) fusion gene in samples from patients with ALL than in samples from patients with AML. Conclusions: We have shown a rapid and effective flow cytometry method that enables the identification of immunophenotype in AL. Moreover, CD2 may constitute a predictive marker for prognosis in patients with AML.